(untitled) (Research, Society and Development, 2025)
This study aims to analyze whether there are accounting inconsistencies in the Balance Sheets of the state of Minas Gerais (MG) for the financial years 2020, 2021, 2022 and 2023, based on the Disclosure Theory. To conduct the research, data were collected from the Brazilian Public Sector Accounting and Tax Information System (SICONFI), the Public Debt Analysis System, Credit Operations, and Guarantees of the Union, States, and Municipalities (SADIPEM), the Integrated View of the Debts of the Union, States, Federal District, and Municipalities website, and the Minas Gerais Transparency Portal. The results indicated the following accounting inconsistencies in the Balance Sheets: inconsistencies between the values of Real Liabilities and Payable Liabilities plus Unprocessed Remaining Payables (RPNP), with the concealment of the RPNP information; discrepancy in SICONFI between the amounts of Current Liabilities and Actual Liabilities, with the exclusion of RPNP from current liabilities; inconsistent debt amounts, which causes discrepancies in the calculation of accounting balances. There were also discrepancies in the values of items that make up the Balance Sheet disclosed on the websites of the Brazilian Public Sector Accounting and Tax Information System (SICONFI) and the Minas Gerais Transparency Portal. It is therefore concluded that the values recorded in the Balance Sheets for the financial years 2020, 2021, 2022 and 2023 do not represent the financial situation of the state of Minas Gerais - MG. Furthermore, the research problem was solved, as accounting inconsistencies were highlighted.